The Right to Friendship - Riofrío Martínez-Villalba, Juan Carlos (2023)
In the academy, voices are beginning to advocate for a more robust and individualized recognition of the right to friendship. It is not that in the past the law has not addressed friendship, but the truth is that, until now, it has only done so tangentially and sporadically. This paper aims to address these gaps and provide a comprehensive overview of where this right should be placed. This will be accomplished by proposing definitions, principles, and rules that govern the matter, as well as the rights and duties related to friendship, albeit in a preliminary manner and for the purpose of discussion. Therefore, we believe that a better understanding of the legal scope and limits of this right will be achieved. Certainly, this proposal in this article is undeniably audacious. However, it has been justified, to the extent possible, in various jurisprudential rulings, declarations of human rights, treaties, and regulations of comparative law. All this legal baggage has been compiled, systematized, and developed here to showcase the convenience of providing a more unwavering and better-organized protection for this right.